Implementasi Komunikasi Lingkungan Dalam Pembelajaran Penggunaan Bank Sampah di Surabaya - Citta Catherine Gozali; Monika Teguh (Jurnal Penelitian Pendidikan IPA, 2025)
Indonesia faces significant waste management challenges, with projected waste production reaching 65.2 million tonnes by 2023. Household waste, contributing 38.4% of the total, is the largest source of waste nationwide. In Surabaya, Indonesia's fifth-highest waste-producing city, the problem is especially critical. One response to this issue is the waste bank program, enabling communities to exchange waste for economic rewards. This study was conducted with the aim of knowing how the implementation of environmental communication in Bank Sampah Manukan Mukti RW 9 in teaching how to use the waste bank to the community. For eight years, this waste bank has fostered community participation, successfully reducing waste by 300-400 kg monthly and raising awareness of household waste management. Using a descriptive qualitative method and a case study approach, data were collected through interviews, observation, and documentation, with analysis based on the Miles and Huberman framework (data reduction, presentation, and conclusion). Findings indicate that activity-based environmental communication effectively sustains community engagement and understanding in waste management. This model can serve as an example for similar initiatives across Indonesia, enhancing local waste reduction efforts through community-driven strategies.